People-centred knowledge management systems and supply chain performance: the case of small and medium enterprises in Zimbabwe - Tarambiwa, E. (Vaal University of Technology, 2021)
The Small and Medium Enterprise (SME) sector has been receiving increased global attention from governments, researchers and management practitioners in both developed and developing nations as a vehicle for economic growth. The Zimbabwean SME sector has been on record as minimising the impact of the economic challenges on the economy thus proving the strategic role played by the SME sector in improving economic growth. Therefore, the Zimbabwean government has high hopes of resuscitating the economy through empowering the SME sector. However, the sector is inundated by challenges that have retarded its effectiveness in achieving the government’s expectations. Some key limitations and challenges include short life span of the SMEs, entrenchment of archaic business practices, lack of financial capitalisation and the failure to adopt a supply chain perspective of business. Although several solutions to the problem have been proposed and implemented, one solution that has not been fully tested relates to how people-centred knowledge management systems (KMSs) can be harnessed to improve the performance of SME supply chains in Zimbabwe. Therefore, the purpose of this study was to investigate the relationships between people-centred KMSs, knowledge sharing and supply chain performance (SCP) in the Zimbabwean SME sector. The study adopted a quantitative research method in which a survey design was implemented in collecting the data that were used to test the relationships on people-centred KMSs (i.e. communities of practice (CoPs), innovation management, organisational culture and social capital); knowledge sharing and SCP (i.e. time-related performance (TRP), cost-related performance (CRP), responsiveness-related performance (RRP) and operation quality-related performance (OQRP). A structured survey questionnaire was designed using measurement scales adapted from extant literature and it was administered to a sample of 580 SME owners, managers and employees who had some prior understanding of knowledge management, information technology and supply chain management. The collected data were analysed using the Statistical Packages for Social Sciences (SPSS) Version 25.0 and the Analysis of Moment Structures (AMOS) Version 25.0 statistical software. The data were analysed using both descriptive and inferential statistics. The statistical techniques used included measures of central tendency, cross-tabulations, factor analysis, multiple linear regression analysis, path analysis and structural equation modelling. The results of the study showed that SME employer qualifications (Kendall-tau = 0.88; p=.000), work experience (Kendall-tau = 0.86; p=.001) and nationality (Kendall-tau = 0.79; p=.010) as well as SME business sector (Kendall-tau = 0.89; p=.000) can be used to predict SME life span in the Zimbabwe SME sector. The results also showed significant relationships between three people-centred KMSs, namely, CoP (β=0.639, t=9.656, p=0.000), innovation management (β =-0.337, t=-8.578, p=0.000) and organisational culture (β=-0.261, t=-4.083, p=0.000) and knowledge sharing. The relationship between social capital and knowledge sharing was insignificant (β=-0.076, t=0.177, p=0.859). Significant relationships were also realised on knowledge sharing and three process-based SCP sub- factors, namely, TRP (β=0.231, t=4.717, p=0.000), CRP (β=-0.082, t=-2.015, p=0.044) and RRP (β=-0.177, t=-3.621, p=0.000). No relationship was found between knowledge sharing and OQRP (β=-0.076, t=0.049, p=0.254). Moreover, knowledge sharing was found to have a full mediation effect on people-centred KMSs and process-based SCP while no mediation effect was found with network-based SCP. The study makes substantial contributions to the existing body of knowledge. Theoretically, it provides in-depth insights of people-centred KMSs in SME SCP for developing countries such as Zimbabwe, which is an under researched area, thus expanding extant literature on the subject. From a knowledge management perspective, the study proposes the utilisation of SMEs’ socio-demographic factors to predict SMEs’ continued existence, thereby enabling financial institutions to offer financial assistance to such businesses with confidence. For governments in developing countries, the study suggests that specific attention should be directed to knowledge-based supply chains that adopt people-centred KMSs and process-based SCP to consider them as a possible alternative in addressing performance challenges in SME sectors.
Ph. D. (Department of Business Administration, Faculty of Management Sciences), Vaal University of Technology.
Keywords: People-centred knowledge management systems; Supply chain performance; Small and medium enterprises; Economic growth; Dissertations, Academic -- South Africa; Small business -- Zimbabwe; Business logistics